2016
DOI: 10.1161/strokeaha.115.011939
|View full text |Cite
|
Sign up to set email alerts
|

Self-Administered Computer Therapy for Apraxia of Speech

Abstract: Speech/language impairments after stroke are subcategorized into aphasia, dysarthria, and apraxia of speech (AOS). AOS is a disorder at the interface of language and speech production, involving breakdown in mapping from abstract linguistic representations to motor plans.1 Typical behaviors include speech errors, loss of automaticity and fluency, and altered timing parameters. 2 In severe cases, patients may be nonverbal. Lesions causing AOS usually occur within the left cortical motor or somatosensory areas. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The results imply that there is potential for improvement from an intensive paradigm based on repeated exposure-test cycles. This could in principle be made home-deliverable and patient-led, an approach that has demonstrable efficacy for improving speech production in similar patient groups ( Varley et al, 2016 ); the tasks employed in this study were automated and computer based. The finding that learning did not generalise across modalities implies that such a therapy would need to use linguistic material, as it would be unlikely to be so well learnt with non-linguistic material or to transfer across domains.…”
Section: Discussionmentioning
confidence: 99%
“…The results imply that there is potential for improvement from an intensive paradigm based on repeated exposure-test cycles. This could in principle be made home-deliverable and patient-led, an approach that has demonstrable efficacy for improving speech production in similar patient groups ( Varley et al, 2016 ); the tasks employed in this study were automated and computer based. The finding that learning did not generalise across modalities implies that such a therapy would need to use linguistic material, as it would be unlikely to be so well learnt with non-linguistic material or to transfer across domains.…”
Section: Discussionmentioning
confidence: 99%
“…Behavior changes in self-controlled practice are believed to be attributed to motivation (Lewthwaite & Wulf, 2012). There is great interest to facilitate selfcontrolled practice (i.e., home practice) (Johnson et al, 2014;Lasker et al, 2008Lasker et al, , 2010 and/or self-controlled therapy using computer-based programs for acquired AOS (Varley et al, 2016). While home practice has been incorporated in multiple MLG treatment studies, the influence of the practice beyond treatment session with clinician is unknown (Ballard et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is reported that how much and what was practiced influenced treatment outcomes more than session dose and was identified as potentially one of the missing ingredients (Cherney, 2012;Togher, 2012). Having a better understanding of specific motivating factors of our clients, could guide our decision to use self-controlled practice and identify the best structure to meet our patient's needs (Varley et al, 2016). Investigations measuring motivating factors would be a welcome area of future research (Raymer & Rothi, in press) and may be one of the missing ingredients to maximize behavioral change for speech motor learning in our clients with acquired AOS.…”
Section: Discussionmentioning
confidence: 99%
“…All intervention stimuli were relevant to everyday talk about experiences, opinions and exchanging information. Participants practiced flexible use of constructions via errorless learning strategies, following the steps used in the SWORD program (Varley et al, 2016;Whiteside et al, 2012).…”
Section: Intervention and Outcome Measuresmentioning
confidence: 99%